Answer:
f(x) - g(x) = -x⁸ + 8x³ + 5x² - 13
General Formulas and Concepts:
Pre-Algebra
Algebra I
Explanation:
Step 1: Define
f(x) = -5x⁹ - x⁸ + 3x³ - 8
g(x) = -5x⁹ - 5x³ - 5x² + 5
Step 2: Find f(x) - g(x)
- Substitute: f(x) - g(x) = -5x⁹ - x⁸ + 3x³ - 8 - (-5x⁹ - 5x³ - 5x² + 5)
- Distribute -1: f(x) - g(x) = -5x⁹ - x⁸ + 3x³ - 8 + 5x⁹ + 5x³ + 5x² - 5
- CBT (x⁹): f(x) - g(x) = -x⁸ + 3x³ - 8 + 5x³ + 5x² - 5
- CBT (x³): f(x) - g(x) = -x⁸ + 8x³ - 8 + 5x² - 5
- CBT (Z): f(x) - g(x) = -x⁸ + 8x³ + 5x² - 13
And we have our final answer!